KONSTRUKSI MAKNA DALAM BUDAYA TRADISI PENGANTIN SAHUR DI DESA PULAU PALAS KECAMATAN TEMBILAHAN HULU KABUPATEN INDRAGIRI HILIR - Muhammad Hadli; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The cultural tradition of bride Suhoor is cultural tradition/habit that descended from generations, developed up to now in the region of the village of the Island District and subdistrict Tembilahan Hulu Palas Indragiri Hilir, the runway is considered a tradition full of values and philosophies that are present in the form of the activities of the party culture of the people's Party, or held as a form of entertainment.Bridal traditions Suhoor conjures the symbols that are understood by the people of the island of palas as part of the social life of the community. Bridal traditions Suhoor already exists since time immemorial followed by youth community which is an annual event in the month of fasting is to awaken the public to Suhoor.This study is focused to find out how the meaning of symbolic traditions bridal Suhoor in-construction and become local wisdom Island village of Palas.Approach this research uses qualitative research methods. To the study of communication Ethnography through symbolic interaction and approaches supported by the theory of social construction of the object of research is the tradition of bride Suhoor activities, Informants are chosen by purposive sampling technique, to informant amounted to 7 persons composed of angah, kades, sekdes, kadus, Suhoor, bridal and participants in society. Research data obtained through interview, observation, documentation, library studies and search data online.To test the validity of the data using the test of credibility. As for the data analysis techniques to reduce data, collecting data, presenting data, draw conclusions and evaluation.Research results show that in the tradition of bridal Suhoor, very much there are values that are contained in its implementation, namely the value of the discussion, mutual values, the values of hospitality, economic value, cultural values, a value parawisata.The meaning contained in the tradition of a Chair has its own meaning Suhoor, namely a pair of bride and groom symbol of happiness, throne, meaning that the young men of the village Island palas which features creativity and cooperation between youth. Any wagon has its own symbolic meaning livelihoods Indragiri Hilir which is coconut farmers.From the tradition of bridal Suhoor obtained conclusions, that the cultural traditions of the bride Suhoor shows symbols that are understood and interpreted by the community together, where cultural values as well as the meaning contained in the It makes this art as the local wisdom of the island village of palas.